Peace Values of the Kajang Ammatoa Tribe and Their Implications for Guidance and Counseling - Hikmah, Muh Syawal; Yusri, Akbar Gibran; Fathan, A As'ad; Mirdan, Moh; Kaffah, Muhammad Silmi; Amsil, Alfin Elkindy (IAIN Kudus, 2025)
The Peace Values of the Kajang Ammatoa Tribe and Their Implications for Guidance and Counseling.Local wisdom in the Kajang tribe of Ammatoa custom is known as Pasang ri Kajang which means ancestral messages from Kajang which are still carried out today. This study aims to examine the values of peace pairs of Kajang ri in the Kajang tribe of Ammatoa custom and how they are applied to guidance and counseling. This study uses a qualitative method with a qualitative descriptive approach to understand social phenomena in depth and comprehensively. From the results of the study, the values of peace in the Kajang pairs were found, including the values of honesty (A'cepat Lambusu), the values of unity and togetherness, mutual respect, respect, and care for each other (A'lemo sibatu a'bulo sipappa tallang sipahua' manyu siparappe mate siroko' bunting sipabasa, lingu sipakainga' sipakatau tau tan sipakasiri; Sipatabe ki; Paka bajiki gau'nu sara-sara makana'nu nanuliliang lanatabayya; Katutui bua babanu imba babanu magimai kadua pajajiannu ri tau toa nu; timbarangngi pau haji padannu tau) and there were also values of conflict or problem resolution (A'borongki). As the application of the values of peace in guidance and counseling services in this study, it was identified in the objectives of basic services in the field of personal and social guidance and counseling as well as the main materials of personal and social guidance.Keywords: Pasang ri Kajang; Peace Values, Ammatoa Tribe, Guidance and Counseling.